2008
DOI: 10.1002/glia.20678
|View full text |Cite
|
Sign up to set email alerts
|

Microglial dystrophy in the aged and Alzheimer's disease brain is associated with ferritin immunoreactivity

Abstract: Degeneration of microglial cells may be important for understanding the pathogenesis of aging-related neurodegeneration and neurodegenerative diseases. In this study, we analyzed the morphological characteristics of microglial cells in the nondemented and Alzheimer's disease (AD) human brain using ferritin immunohistochemistry. The central hypothesis was that expression of the iron storage protein ferritin increases the susceptibility of microglia to degeneration, particularly in the aged brain since senescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
194
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(226 citation statements)
references
References 56 publications
17
194
1
2
Order By: Relevance
“…Additionally, an outward rectifier K + channel called Kv1.3 has been found to increase expression in dystrophic microglia in aged mouse brains [146]. Dystrophic microglia become more prevalent with human aging and have been found to increase in a variety of diseases including AD [147] and Huntington's disease [148]. There is also evidence that the chronic inflammation that accompanies neurodegeneration leads to local increases in microglia with high iron and ferritin content, possibly due to iron scavenging [149].…”
Section: Microglia and Agingmentioning
confidence: 99%
“…Additionally, an outward rectifier K + channel called Kv1.3 has been found to increase expression in dystrophic microglia in aged mouse brains [146]. Dystrophic microglia become more prevalent with human aging and have been found to increase in a variety of diseases including AD [147] and Huntington's disease [148]. There is also evidence that the chronic inflammation that accompanies neurodegeneration leads to local increases in microglia with high iron and ferritin content, possibly due to iron scavenging [149].…”
Section: Microglia and Agingmentioning
confidence: 99%
“…Microglia density in the CNS tissue increases with age (Poliani et al 2015), but a subset of these cells in humans, highly expressing ferritin, shows signs of dystrophy or senescence, characterized by a reduction and beading of cell processes (Lopes et al 2008). Microglia senescence is particularly prominent in the brain of aging patients with progressive MS and is associated with a prominent loss of microglia and macrophages in inactive lesions in comparison to the normal-appearing white matter (Hametner et al 2013;Zrzavy et al 2017).…”
Section: Iron-related Microglia Pathology-microglia Senescencementioning
confidence: 99%
“…27) Although there are limited reports on the effects of Mninduced toxicity on glial cells, some studies suggested that self-produced ROS can stimulate degradation of ferritin in microglia and subsequent microglial cell death. 29,30) However, little is known about the molecular mechanisms responsible for Mn toxicity in microglia.…”
Section: Discussionmentioning
confidence: 99%